1996
DOI: 10.2337/diacare.19.12.1430
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Simulated Altitude on the Performance of Five Blood Glucose Meters

Abstract: Except for the Accu-Chek Easy, low barometric pressure underestimated the BGM results in comparison with measurements taken at simulated low altitudes. The lack of accuracy and consistency of performance > 2,000 m should be known by diabetic patients practicing sports activities, such as trekking or skiing at high altitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 8 publications
1
18
2
1
Order By: Relevance
“…[40][41][42][43][44] Both, under-and overestimated BG values have been observed, being a relatively lowered pO 2 the main reason for these measurement deviations. 22 Under decreasing pO 2 clinically relevant deviations with a risk of treatment errors have been demonstrated with some meters, 41,45 an effect normally related to increased BG readings. In a study conducted in Tanzania, 3 BG meters taken to Mt Kilimanjaro (>5800 m) showed BG readings of 50, 214, and 367 mg/dL on the same sample.…”
Section: Altitudementioning
confidence: 99%
“…[40][41][42][43][44] Both, under-and overestimated BG values have been observed, being a relatively lowered pO 2 the main reason for these measurement deviations. 22 Under decreasing pO 2 clinically relevant deviations with a risk of treatment errors have been demonstrated with some meters, 41,45 an effect normally related to increased BG readings. In a study conducted in Tanzania, 3 BG meters taken to Mt Kilimanjaro (>5800 m) showed BG readings of 50, 214, and 367 mg/dL on the same sample.…”
Section: Altitudementioning
confidence: 99%
“…Low blood oxygen tension theoretically would cause glucose oxidase-based meters to over-read, which was reported to be as much as 6%-15% in one study where glucose dehydrogenase-based strips were more accurate at altitude (Oberg and Ostenson, 2005), whereas other studies have shown the converse at moderate altitude (Olateju et al, 2012). Several studies confirm over-or under-reading at altitude of both reagents (Bilen et al, 2007;Fink et al, 2002;Gautier et al, 1996;Giordano et al, 1989;Olateju et al, 2012;Pavan et al, 2004;Pecchio et al, 2000) and discrepancy between simulated and real altitude (de Mol et al, 2010). Technological improvement may reduce these errors (Bailey et al, 2012;Lock et al, 2011) and in any case the clinical effect would appear minimal unless over-reading on the borders of hypoglycemia.…”
Section: Glucometersmentioning
confidence: 89%
“…Although these findings have not been confirmed scientifically, most climbers rely on this shared information for high altitude BG monitoring. Studies on the reliability of these devices have been performed at altitudes below 4000 m or with models that are now outdated (Giordano et al, 1989;Piepmeier et al, 1995;Gautier et al, 1996;Fanghanel et al, 1998;Pecchio et al, 2000;Williams and Petoskey, 2000). Hemoconcentration, very frequent at altitude, may cause an underestimation in the results (Barreau and Buttery, 1988).…”
Section: Altitude Environment and Dm-1 Managementmentioning
confidence: 97%